1999
DOI: 10.1039/a900819e
|View full text |Cite
|
Sign up to set email alerts
|

Location of Li(I), Cu(II) and Cd(II) in heated montmorillonite: evidence from specular reflectance infrared and electron spin resonance spectroscopies

Abstract: Specular reflectance infrared and electron spin resonance spectroscopies were employed for the analysis of the sites of Li(), Cu() and Cd() cations fixed in the structure of montmorillonite from Jels ˇovy ´Potok (Slovakia) upon heating for 24 h at 300 °C. Li() cations are trapped in two different sites: in the previously vacant octahedra and in the hexagonal holes of the tetrahedral sheet. Cu() cations are fixed deep in the hexagonal holes. They substantially affect the vibration modes of Si-O bonds an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…Such sites can occur in the structure or at the inner surface, i.e. interlayers and hexagonal cavities of the hectorite (Clementz et al, 1973;Luca et al, 1991;Karakassides et al, 1999;Spagnuolo et al, 2004). The spectral parameters g || = 2.42 and A || = 10 mT, obtained from low-temperature measurements, are similar to the parameters determined by Luca et al (1991) and assigned to structure-bound Cu(II).…”
Section: Cu In the Modified Starting Materialssupporting
confidence: 61%
“…Such sites can occur in the structure or at the inner surface, i.e. interlayers and hexagonal cavities of the hectorite (Clementz et al, 1973;Luca et al, 1991;Karakassides et al, 1999;Spagnuolo et al, 2004). The spectral parameters g || = 2.42 and A || = 10 mT, obtained from low-temperature measurements, are similar to the parameters determined by Luca et al (1991) and assigned to structure-bound Cu(II).…”
Section: Cu In the Modified Starting Materialssupporting
confidence: 61%
“…However, some uncertainty still exists over the precise location of the lithium ions within the clay framework. It has been suggested that the cations migrate from the interlayer (Figure a) into the ditrigonal cavities of the tetrahedral layer (Figure b), the vacant octahedral sites (Figure c), or both of these.
1 Lithium montmorillonite unit cell. Upon thermal treatment, the lithium cations are thought to migrate from the interlayer (a) into the ditrigonal cavities of the tetrahedral layer (b), the vacant octahedral sites (c), or both of these.
…”
Section: Introductionmentioning
confidence: 99%
“…The peak broadening of the hybrids compared to the neat clays also suggests that surface modification induces a stacking disorder in the clay particles. The collapsed spacing observed for NAN2SI6 is due to dehydration and reversible migration of the sodium ions to the hexagonal cavities of the tetrahedral silicate sheets upon thermal drying . However, no collapse was observed for the fluorohectorite layers after the same treatment.…”
Section: Resultsmentioning
confidence: 92%
“…In addition, the absorption bands in the low region spectra (1000−500 cm -1 ) become more distinct than those present in the pristine clays. These peaks can be assigned to the Si−O groups of the clay framework and grafted organosiloxane. , No changes are observed above 3500 cm -1 , where typically the −OH stretching vibration appears. The −OH groups that are buried within the layered framework overwhelm the number of edge-located groups.…”
Section: Resultsmentioning
confidence: 99%